Aortic Valve Calcification and Risk of Stroke: The Rotterdam Study. Issue 11 (November 2016) - Bos, Daniel; Bozorgpourniazi, Atefeh; Mutlu, Unal; Kavousi, Maryam; Vernooij, Meike W.; Moelker, Adriaan; Franco, Oscar H.; Koudstaal, Peter J.; Ikram, M. Arfan; van der Lugt, Aad
Abstract : Background and Purpose—: It remains uncertain whether aortic valve calcification (AVC) is a risk factor for stroke. Methods—: From the population-based Rotterdam Study, 2471 participants (mean age: 69.6 years; 51.8% women) underwent computed tomography to quantify AVC. We assessed prevalent stroke and continuously monitored the remaining participants for the incidence of stroke. Logistic and Cox regression models were used to investigate associations of AVC with prevalent stroke and risk of incident stroke. Results—: AVC was present in 33.1% of people. At baseline, 97 participants had ever suffered a stroke. During 18 665 person-years of follow-up (mean: 7.9 years), 135 people experienced a first-ever stroke. The presence of AVC was not associated with prevalent stroke (fully adjusted odds ratio: 0.97 (95% confidence interval, 0.61–1.53]) or with an increased risk of stroke (fully adjusted hazard ratio: 0.99 (95% confidence interval, 0.69–1.44]). Conclusions—: Although AVC is a common finding in middle-aged and elderly community-dwelling people, our results suggest that AVC is not associated with an increased risk of stroke. Abstract : Supplemental Digital Content is available in the text.